Peran farmasis di industri obat di Indonesia sebagai gambaran lapangan kerja alumni farmasi Universitas Mataram - Windah Anugrah Subaidah; Wahida Hajrin; Yohanes Juliantoni (Universitas Mataram, 2023)
The unemployment rate rises every year, leading people to seek information for the purpose of gaining and providing jobs, which can be achieved by attending university. Given its bright future prospects, pharmacy is a popular field of study. A pharmacist may work in the industrial sector; according to Ministry of Health data from 2019, Indonesia had up to 230 industry pharmaceuticals. The rise of Indonesia's pharmaceutical industry will require a huge number of employees, especially experienced pharmaceutical professionals. Unfortunately, the results of tracer studies for Pharmacy graduates from the University of Mataram who work in the industrial sector are still quite low. According to a similar survey, a lack of interest in pharmaceutical graduates can be related to a lack of knowledge about the pharmaceutical industry. The purpose of this community service activity is to encourage pharmacy students to work in the pharmaceutical industry. Service activities can be carried out in three stages: preparation, implementation, monitoring, and evaluation. The results of the activity showed that the participants were enthusiastic about the program, as seen in the way they engaged in asking questions and responding to the question from the committee. The result of the evaluation revealed that 93.2% of the participants planned to work in the pharmaceutical industry. As a result, this community service activity is seen to have the potential to help inspire and encourage pharmacy students to pursue careers in the pharmaceutical industry.